Prevalence and genotyping distribution of Enterocytozoon bieneusi in diarrheic pigs in Chongqing and Sichuan provinces, China - Ghebremichael, Samson Teweldeberhan; Meng, Xianzhi; Wei, Junhong; Yang, Yujiao; Huang, Qingyuan; Luo, Lie; Xiang, Heng; Chen, Jie; Abo-Kadoum, M. A.; Li, Tian; Liu, Xiao; Bao, Jialing; et al. (Frontiers in Microbiology, 2022)
The microsporidian fungal pathogen Enterocytozoon bieneusi is a unicellular parasite that infects humans and various animals, including pigs. Currently, there are few data on E. bieneusi infection a in diarrheic pigs in Chongqing and Sichuan Provinces, China. This study aims to determine the prevalence and genotype distribution of E. bieneusi in diarrheic pigs. In total, 514 fecal samples from diarrheic pigs were obtained from 14 large-scale farms in Chongqing and Sichuan Provinces (326 suckling pigs, 17 weaned pigs, 65 fattening pigs, and 106 sows). To identify the E. bieneusi genotypes, genomic DNA was isolated from the samples and tested by nested PCR, targeting the internal transcribed spacer region of the rRNA followed by DNA sequence analysis. The overall prevalence of E. bieneusi was 79.8% (410/514), with rates of 84.9% (90/106) in sows and 64.7% (11/17) in weaned pigs. We found 61 different genotypes, including seven known genotypes (E, F, CHG1, Peru8, CAF1, B, and BEB17) and 54 novel genotypes. These 54 new genotypes are variants of eight known genotypes (SDD2, A, B, HLJD-IV, PigSpEb1, O, JLD-I, and BEB17) based on their sequence similarities. Phylogenetically, all of the identified genotypes clustered with counterparts belonging to Group 1 and Group 2 of E. bieneusi. Therefore, we found a higher prevalence of E. bieneusi in sows than in preweaned and weaned pigs. These findings indicate that diarrheic pigs could be a potential reservoir host, which can contaminate the environment and be a source of microsporidia in humans and other animals.